EKSEKUSI OBJEK JAMINAN FIDUSIA OLEH KREDITOR SEPARATIS DALAM PERKARA KEPAILITAN - Faisal, Fedhli (Collegium Studiosum Journal, 2024)
This study examines the legal implications of the execution of fiduciary guarantees in bankruptcy, focusing on the rights of secured creditors and the role of the curator. According to Article 59(1) of the Bankruptcy and Suspension of Debt Payment Obligations Law, secured creditors holding fiduciary guarantees are required to exercise their execution rights within no later than two months from the commencement of the state of insolvency. If not exercised, these execution rights are transferred to the curator. This research adopts a statutory approach and a case approach, analysing the bankruptcy case Number 269 K/Pdt-Sus-Pailit/2024. In this case, the secured creditor executed the fiduciary object beyond the prescribed time limit, prompting the curator to file a lawsuit against the action as an unlawful act in the Semarang Commercial Court. The court ruled that the creditor's actions were unlawful and ordered the creditor to return the disputed objects, including the vehicle registration certificate (BPKB) and a four-wheeled vehicle. This decision was upheld by the Supreme Court, which referred to Constitutional Court Decision Number 18/PUU/XVII/2019. The study highlights the importance of creditors' compliance with execution rules and the role of the judiciary in safeguarding the interests of parties involved in bankruptcy.